Assessment of Development Rate and Spatial Distribution of Industrial Cities in Urban Conurbation of Isfahan - Seyed Sina Rahnamaei; Dr.Hamid Saberi; Dr.Amir Gandomkar (جغرافیا و آمایش شهری منطقه‌ای, 2017)
The purpose of this study was to evaluate the development and spatial distribution of industrial towns in Isfahan city. The research method is descriptive-analytic. Isfahan city complex based on Physical divisions of housing and urban planning consists of parts of 7 cities of Isfahan, including Najafabad, Mobarakeh, Lenjan, Falavarjan, Khomeini Shahr, Borkhar and Meyma, with a total area of ​​8347 square kilometers. Topsis model was used to study the development level and the spatial distribution of industrial towns in Isfahan city complex.  In this method, for forming the decision making matrix, 15 existing industrial towns were used in the city complex as decision options and eight effective indicators were used as decision making  criteria. Then the final ranking was done by weighting the indices using the Topsis model with entropy model. The results show that  out of 15 existing industrial towns, the only industrial city of Mahmoudabad, Isfahan with a score of 0.948 has the highest score (developed), the two  Mobarakeh and Ashtarjan industrial towns has  a semi-developed state, and 12 other settlements, have a less developed status. The spatial distribution of industrial cities of the urban settlements at the level of the towns with a coefficient of 145% was assessed as  unequal.